Essentials of psycho-analysis / transleted by James Strachey - "Freud, Sigmund" (London, 2005)
The Essentials of Psycho-analysis is the definitive collection of Sigmund Freud's writing. It covers the themes that Freud explored in his work from the meaning of dreams and the concept of the unconscious, instinctual and sexual life to the structure of the personality. Beautifully written and endlessly fascinating, the pieces collected here are the perfect guide to the principle concepts of psycho-analysis.
Keywords: Psychology